2018
DOI: 10.1111/ecc.12900
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Chinese version of the revised illness perception questionnaire for breast cancer-related lymphedema

Abstract: The aim of this study was to modify and test the Chinese version of the Revised Illness Perception Questionnaire to measure the illness perception of breast cancer-related lymphedema among breast cancer survivors. Before the investigation, identity and causal subscales were modified and the wording of the remaining scales was also adjusted. The psychometric properties of this instrument was evaluated using the technique of explore and confirmatory factor analysis. Data from 203 breast cancer survivors was ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Illness Perception Illness perception was measured by the Illness Perception Questionnaire Revised (IPQ-R) (Hale et al 2007;Moss-Morris et al 2002). The IPQ-R has been validated in Chinese population (Huang et al 2019). Four subscales of the IPQ-R were used: personal control (four items, e.g., the course of my illness depends on me), treatment control (five items, e.g., my treatment can control my illness), timeline cyclical (four items, e.g., my illness is unpredictable), and consequences (six items, e.g., my illness has major consequences on my life).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illness Perception Illness perception was measured by the Illness Perception Questionnaire Revised (IPQ-R) (Hale et al 2007;Moss-Morris et al 2002). The IPQ-R has been validated in Chinese population (Huang et al 2019). Four subscales of the IPQ-R were used: personal control (four items, e.g., the course of my illness depends on me), treatment control (five items, e.g., my treatment can control my illness), timeline cyclical (four items, e.g., my illness is unpredictable), and consequences (six items, e.g., my illness has major consequences on my life).…”
Section: Methodsmentioning
confidence: 99%
“…1 Self-compassion (total score, positive and negative self-compassion) normative data from Raes et al 20112 Consequence, personal control, treatment control, and timeline cyclical normative data fromWu et al 2018 andHuang et al 2019 3 Depressive symptoms' normative data fromWang et al 2014 4 Anxiety symptoms' normative data fromMarteau and Bekker 1992 …”
mentioning
confidence: 99%
“…Illness perception regarding BCRL IP regarding BCRL was measured by a BCRL-speci c Chinese version of the Illness Perception Questionnaire-Revised [CIPQ-R(BCRL)] [11]. It consists of 9 dimensions.…”
Section: Instruments Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…IP is the main concept of the Common Sense Model (CSM) [9,10] and refers to individuals' views on symptoms, risk factors, time frame (development and duration), consequences, controllability, self-understanding and emotional representations of disease [11,12]. Numerous studies have demonstrated the signi cant impact of IP on patients' health behaviors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 Moreover, patients’ perception, cognition, and interpretation of the causes, timeline, consequences, and control of illness could affect their medical advice seeking and treatment compliance. 22 For patients, the more perception of illness, the more serious perceived illness, and the more negative attitude toward physicians. 23 Therefore, we hypothesized that the PPOSS was negatively correlated with the WFOTS, and positively correlated with the IUS-12 and the BIPQ.…”
mentioning
confidence: 99%